Effect of early age thermal challenge on growth performance, haematological parameters and carcass yield of Indigenous Guinea fowl (Numida meleagris) - Orounladji, Boko, Michel (My University, 2022)
This study aimed to evaluate the effect of thermal stress on haematological profile and carcass yield of guinea fowl (GF). A total of 180 one-day old GF keets were assigned to 3 treatments, having 4 replicates of 15 birds each. The treatments were: control (T1); mild heat stress for 6h/day (T2), and high heat stress for 8h/day (T3). Data were collected on weekly body weights, feed intake and feed conversion ratio of the birds. At 6-weeks old, blood samples were collected from 8 GF for determination of haematological profile. At 14-weeks old, 8 birds were also slaughtered per treatment to evaluate relative organ weights, carcass characteristics and immune response. Results showed that the body weight gain and feed intake of the birds of T1 and T2 were similar and significantly higher than that of T3 at week 1 of age. The FCR of the birds in T1 and T2 were also better at this stage. Lymphocyte counts were higher (p<0.01) in the birds of T2 (95 103/mL) than those of the control (93.33 103/mL) and T3 (93.33 103/mL). The weights of lymphoid organs of T2 and T3 birds were higher (p<0.05) than those of the control group. It was concluded that exposure of keets to heat stress for 8h/day had adverse effects on growth performance at the early age but this effect faded with age. The thermal manipulation in this study didn’t influence the carcass yield but improved the weights of lymphoid organs of indigenous GF, indicating a better thermo-tolerance.
Supplemental Materials: https://osf.io/qgwur/
Keywords: Carcass yield; Growth performance; Guinea fowl; Haematological parameters; Heat stress; Immune organs